Characterization of METRNβ as a novel biomarker of Coronavirus disease 2019 severity and prognosis - Gao, Xun; Chan, Paul Kay-Sheung; Wong, Katie Ching-Yau; Ng, Rita Wai-Yin; Yeung, Apple Chung-Man; Lui, Grace Chung-Yan; Ling, Lowell; Hui, David Shu-Cheong; Huang, Danqi; Wong, Chun-Kwok (Frontiers in Immunology, 2023)
Introduction: Coronavirus disease 2019 (COVID-19) is increasing worldwide, with complications due to frequent viral mutations, an intricate pathophysiology, and variable host immune responses. Biomarkers with predictive and prognostic value are crucial but lacking. Methods: Serum samples from authentic and D614G variant (non-Omicron), and Omicron-SARS-CoV-2 infected patients were collected for METRNβ detection and longitudinal cytokine/chemokine analysis. Correlation analyses were performed to compare the relationships between serum METRNβ levels and cytokines/chemokines, laboratory parameters, and disease severity. Receiver operating characteristic (ROC) curves and Kaplan-Meier survival curves were used to evaluate the predictive value of METRNβ in COVID-19. Results: The serum level of METRNβ was highly elevated in non-Omicron-SARS-CoV-2 infected patients compared to healthy individuals, and there was a positive correlation between METRNβ and disease severity. METRNβ concentration returned to baseline levels after antiviral treatment. Longitudinal analysis of cytokine/chemokine profiles revealed a positive correlation between METRNβ and pro-inflammatory cytokines such as IL6, and an inverse correlation with soluble CD40L (sCD40L). ROC curve showed that a baseline METRNβ level of 1886.89 pg/ml distinguished COVID-19 patients from non-infected individuals with an AUC of 0.830. Higher METRNβ was associated with increased mortality. These findings were validated in a second and third cohort of COVID-19 patients identified in a subsequent wave. Discussion: Our study uncovered the precise role of METRNβ in predicting the severity of COVID-19, thus providing a scientific basis for further evaluation of the role of METRNβ in triage therapeutic strategies.